1989
DOI: 10.1093/bja/62.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propofol on the Malignant Hyperthermia Susceptible Pig Model

Abstract: Anaesthetic techniques for malignant hyperthermia susceptible (MHS) patients should include drugs which do not trigger MH and provide stress free conditions. Thus all new drugs should be screened for their susceptibility to trigger MH. We have screened propofol, using the MHS pig model. In none of the animals exposed to propofol, were there signs of MH, even after challenge with suxamethonium. However, the same animals developed MH when exposed to halothane alone or with suxamethonium. Despite the problems of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…For patients known or suspected of being susceptible, potential triggers must be avoided and alternative methods of anesthesia applied, such as with propofol and xenon. 8,29,57,58,83,99 During a crisis, treatment consists of early administration of dantrolene. 82 This lipid-soluble hydantoin derivative acts by inhibiting the release of calcium from the sarcoplasmic reticulum, therefore inhibiting muscle contractures induced by triggering agents and normalizing myoplasmic calcium concentration.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…For patients known or suspected of being susceptible, potential triggers must be avoided and alternative methods of anesthesia applied, such as with propofol and xenon. 8,29,57,58,83,99 During a crisis, treatment consists of early administration of dantrolene. 82 This lipid-soluble hydantoin derivative acts by inhibiting the release of calcium from the sarcoplasmic reticulum, therefore inhibiting muscle contractures induced by triggering agents and normalizing myoplasmic calcium concentration.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Previous reports have shown that propofol is safe as a general anaesthetic for MHS patients [4][5][6] . In these studies propofol was examined in MHS animals or humans by measuring general anaesthesia or by examining human muscle contraction.…”
mentioning
confidence: 90%
“…1992 swine anaesthesia studies, but no details of anaesthetic technique or monitoring were included. 4 We decided to investigate further the response of human MHS muscle in vitro, and the response of human MHS patients to bolus doses of propofol prior to conducting studies on the safety of propofol infusion anaesthesia in MHS individuals.…”
Section: Accepted For Publication January 13 1992mentioning
confidence: 99%